Calcification of the ligamentum flavum in the thoracolumbar spine: an unusual cause of compressive myelopathy - João Augusto dos Santos Martines; Brenda Margatho Ramos Martines; Cláudio Campi de Castro; José de Arimatéia Batista Araújo Filho; Lorena Elaine Amorim Pinto (University of São Paulo, 2012)
The focal calcification or ossification of the ligamentum flavum is a rare cause of thoracic myelopathy and most often occurs among individuals of Japanese descent. It is rare in other ethnic groups and in individuals below the age of 50. It is most often described at the lower thoracic level, being uncommon in the lumbar region and rare in the cervical region. Here, we present the case of a 44-year-old White female patient who sought medical attention with an eightmonth history of paraesthesia of the lower limbs and progressive difficulty in walking. The clinical profile, together with computed tomography and nuclear magnetic resonance imaging of the spine, led to a diagnosis of compressive thoracic myelopathy due to ossification of the ligamentum flavum in the thoracic and lumbar spine. The patient underwent laminectomy and dissection of some of the affected ligamentum flavum, without any intraoperative complications. After three months of clinical follow-up, the patient had progressed favorably, having no sensory complaints and again becoming ambulatory.